Professional hazards in operating room: effect of anesthetic agents - Rosasco, Carlos L (Cirugía del Uruguay, 1976)
When an operating room is not adequately conditioned, a certain amount of anesthetic gases invade its environment. Their inhalatfon in subanesthetic quantities but on repeated occasions, presents a series of hazards for operating room personnel. The paper analyzes their main toxica! effects on the different parenchymae and suggests a series of measures aimed at reducing pollution and its consequences.